Uncertainty in Weighting Formulary Apportionment Factors and Its Impact on After-Tax Income of Multinational Groups - Ortmann, Regina

OnlineRePair: A Recompressor for XML Structures - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas; Maneth, Sebastian (2015 Data Compression Conference)

ECST – Extended Context-Free Straight-Line Tree Grammars - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas; Jeromin, Markus (Data Science - 30th British International Conference on Databases, BICOD 2015)

Digitale Analyse Graphischer Literatur - Dunst, Alexander; Hartel, Rita; Hohenstein, Sven; Laubrock, Jochen (DHd-Tagung 2015 - Von Daten zu Erkenntnissen)

Fatigue Strength Prediction for Titanium Alloy TiAl6V4 Manufactured by Selective Laser Melting - Leuders, Stefan; Vollmer, Malte; Brenne, Florian; Tröster, Thomas; Niendorf, Thomas (Metallurgical and Materials Transactions A)

Fast fuzzy pattern tree learning for classification - Senge, Robin; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

From knowledge-based to data driven fuzzy modeling: Development, criticism and alternative directions - Hüllermeier, Eyke (Informatik Spektrum)

Does machine learning need fuzzy logic? - Hüllermeier, Eyke (Fuzzy Sets and Systems)

On the Bayes-optimality of F-measure maximizers - Waegeman, W.; Dembczynski, K.; Jachnik, A.; Cheng, W.; Hüllermeier, Eyke (Journal of Machine Learning Research)

Recovery analysis for adaptive learning from non-stationary data streams: Experimental design and case study - Shaker, A.; Hüllermeier, Eyke (Neurocomputing)

Directly comparing entanglement-enhancing non-Gaussian operations - Bartley, Tim; Walmsley, Ian A (New Journal of Physics)

Partial hardening of new press hardenable steels - Marten, Thorsten; Block, Holger; Tröster, Thomas

Multi-axial Material Testing at High Strain Rates in High Speed Cupping Tests - Weiß Borkowski, Nathalie; Marten, Thorsten; Block, Holger; Tröster, Thomas

Bestimmung und Optimierung von Eigenspannungen in hybriden Werkstoffsystemen aus Metall und Faserverbundkunststoff (FVK) - Frantz, M.; Lauter, C.; Wang, Z.; Tröster, Thomas

Kennwertermittlung an Faserverbundkunststoffen für Crashsimulationen mit dem FE-Solver LS-Dyna - Reuter, C.; Tröster, Thomas; Lauter, C.

Fatigue life prediction for metals processed by Selective Laser Melting using finite element analyses - Reschetnik, W.; Leuders, S.; Riemer, A.; Tröster, Thomas; Richard, H. A.; Niendorf, T.

Intrinsic Manufacturing of Metal-FRP-Hybrid Structural Automotive Components by Resin Transfer Moulding - Wang, Z.; Lauter, C.; Sanitther, B.; Frantz, M.; Tröster, Thomas

Methodology for the Product Engineering of Lightweight Structures in Multi-Material Design - Lauter, C.; Wang, Z.; Tröster, Thomas; Brandis, R.; Köchling, D.

Fatigue Behaviour of a Structural Component Manufactured by Selective Laser Melting and Investment Casting - Leuders, S.; Meiners, S.; Taube, A.; Tröster, Thomas; Niendorf, T.

Material follows form follows function - Wingenbach, Nils; Tröster, Thomas

Efficient Biomimetic Hydroxylation Catalysis with a Bis(pyrazolyl)imidazolylmethane Copper Peroxide Complex - Wilfer, Claudia; Liebhäuser, Patricia; Hoffmann, Alexander; Erdmann, Hannes; Grossmann, Oleg; Runtsch, Leander; Paffenholz, Eva; Schepper, Rahel; Dick, Regina; Bauer, Matthias; Dürr, Maximilian; Ivanović-Burmazović, Ivana; et al. (Chemistry - A European Journal)

Dynamic network reconfiguration in wireless DenseNets with the CROWD SDN architecture - Auroux, Sébastien; Draxler, Martin; Morelli, Arianna; Mancuso, Vincenzo (2015 European Conference on Networks and Communications (EuCNC))

MCB – A multi-channel beaconing protocol - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (Ad Hoc Networks)

Linear and Competitive Strategies for Continuous Robot Formation Problems - Degener, Bastian; Kempkes, Barbara; Kling, Peter; Meyer auf der Heide, Friedhelm (ACM Transactions on Parallel Computing)

Towards Gathering Robots with Limited View in Linear Time: The Closed Chain Case - Abshoff, Sebastian; Andreas Cord-Landwehr, Andreas; Jung, Daniel; Meyer auf der Heide, Friedhelm (ArXiv: 1501.04877)
In the gathering problem, n autonomous robots have to meet on a single point. We consider the gathering of a closed chain of point-shaped, anonymous robots on a grid. The robots only have local knowledge about a constant number of neighboring robots along the chain in both directions. Actions are performed in the fully synchronous time model FSYNC. Every robot has a limited memory that may contain one timestamp of the global clock, also visible to its direct neighbors. In this synchronous time model, there is no limited view gathering algorithm known to perform better than in quadratic runtime. The configurations that show the quadratic lower bound are closed chains. In this paper, we present the first sub-quadratic---in fact linear time---gathering algorithm for closed chains on a grid.

Analyse integral erfasster rotationssymmetrischer Schallwechseldruckverteilungen in Schlierenabbildungen - Olfert, Sergei; Henning, Bernd

On the optimal configuration of triple-ring-electrodes on piezoceramic transducers towards increased parameter sensitivity of impedance - Kulshreshtha, Kshitij; Jurgelucks, Benjamin; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Analyse integral erfasster Schallwechseldruckverteilungen in Schlierenabbildungen - Olfert, Sergei; Henning, Bernd (XXIX Messtechnisches Symposium)

On the optimal configuration of triple-ring-electrodes on piezoceramic transducers towards increased parameter sensitivity of impedance - Jurgelucks, Benjamin; Kulshreshtha, Kshitij; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Model based sensitivity analysis in the determination of viscoelastic material properties using transmission measurements through circular waveguides - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd
Several ultrasonic approaches for material determination are formulated in terms of an (nonlinear) inverse problem, e.g. immersion technique (Castaings et al. (2000)) or plate-waveguide techniques (Marzani et al. (2012)). In this contribution we focus on cylindrical waveguides for ultrasonic material determination and especially on the sensitivity of recorded transmission signals to the material properties. We utilize composite scaled sensitivities to determine the information content that can be achieved by the setup to certain parameters and discuss the limitations of the approach.
Keywords: Sensitivity inverse problem ultrasonic material determination

Transient modeling of ultrasonic guided waves in circular viscoelastic waveguides for inverse material characterization - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd (Measurement Science and Technology)
In this contribution, we present an efficient approach for the transient and time-causal modeling of guided waves in viscoelastic cylindrical waveguides in the context of ultrasonic material characterization. We use the scaled boundary finite element method (SBFEM) for efficient computation of the phase velocity dispersion. Regarding the viscoelastic behavior of the materials under consideration, we propose a decomposition approach that considers the real-valued frequency dependence of the (visco-)elastic moduli and, separately, of their attenuation. The modal expansion approach is utilized to take the transmitting and receiving transducers into account and to propagate the excited waveguide modes through a waveguide of finite length. The effectiveness of the proposed simulation model is shown by comparison with a standard transient FEM simulation as well as simulation results based on the exact solution of the complex-valued viscoelastic guided wave problem. Two material models are discussed, namely the fractional Zener model and the anti-Zener model; we re-interpret the latter in terms of the Rayleigh damping model. Measurements are taken on a polypropylene sample and the proposed transient simulation model is used for inverse material characterization. The extracted material properties may then be used in computer-aided design of ultrasonic systems.
Keywords: viscoelasticity; ultrasonics; guided waves; inverse problem; scaled boundary finite element method

Transient modeling of ultrasonic guided waves in circular viscoelastic waveguides for inverse material characterization - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd (Measurement Science and Technology)

Increasing the sensitivity of electrical impedance to piezoelectric material parameters with non-uniform electrical excitation. - Kulshreshtha, Kshitij; Jurgelucks, Benjamin; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten (Journal of Sensors and Sensor Systems)

Schallfeldcharakterisierung mittels Schlierentechnik - Olfert, Sergei; Henning, Bernd

Utilizing guided acoustic waves to measure dispersive material properties of polymers - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (AMA~Conferences 2015)
This contribution will give a short introduction to the most important mechanic and acoustic parameters that are necessary to model and simulate frequency dependent sound propagation (dispersion) in isotropic but linear viscoelastic materials. Furthermore, several experimental techniques to measure these parameters will be discussed, like the dynamic-mechanical analysis and transient ultrasonic techniques. Finally it will be shown how to use the determined material parameters for the simulation of transient signals in a highly attenuative acoustic waveguide.

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Weak and strong interactions between dark solitons and dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Resonant radiation from oscillating higher order solitons - Driben, R.; Yulin, A. V.; Efimov, A. (Optics Express)

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Weak and strong interactions between dark solitons and dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Resonant radiation from oscillating higher order solitons - Driben, R.; Yulin, A. V.; Efimov, A. (Optics Express)

Didaktische und organisatorische Strukturierungen von Micro-Learning – Konzeption und Umsetzungsbeispiele aus den OPALESCE Learning Units - Beutner, Marc; Pechuel, Rasmus; Teine, Matthias (Kölner Zeitschrift für Wirtschaft und Pädagogik)

A High Performance SEU Tolerant Latch - Huang, Zhengfeng; Liang, Huaguo; Hellebrand, Sybille (Journal of Electronic Testing - Theory and Applications (JETTA))

Effiziente Auswahl von Testfrequenzen für den Test kleiner Verzögerungsfehler - Hellebrand, Sybille; Indlekofer, Thomas; Kampmann, Matthias; Kochte, Michael; Liu, Chang; Wunderlich, Hans-Joachim
Keywords: Workshop

Adaptive Playouts in Monte-Carlo Tree Search with Policy-Gradient Reinforcement Learning - Graf, Tobias; Platzner, Marco (Advances in Computer Games: 14th International Conference, ACG 2015, Leiden, The Netherlands, July 1-3, 2015, Revised Selected Papers)

Copolymer-bound phase change materials for household refrigerating appliances: experimental investigation of power consumption, temperature distribution and demand side management potential - Sonnenrein, G.; Baumhögger, Elmar; Elsner, A.; Fieback, K.; Morbach, A.; Paul, A.; Vrabec, J. (International Journal of Refrigeration)

Burst design and signal processing for the speed of sound measurement of fluids with the pulse-echo technique - Dubberke, Frithjof H.; Baumhögger, Elmar; Vrabec, Jadran (Review of Scientific Instruments)

Localization Length Index and Subleading Corrections in a Chalker-Coddington Model: A Numerical Study - Nuding, Win; Klümper, Andreas; Sedrakyan, Ara (Physical Review B)

Application of Automatic Differentiation for the inverse parameter identification of complex-valued forward models - Webersen, Manuel; Bause, Fabian; Henning, Bernd

Identification of temperature-dependent model parameters of ultrasonic piezo-composite transducers - Webersen, Manuel; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (AMA Conferences 2015)
When performing measurements, the effects of the measurement system itself on the measured data generally must be eliminated. Consequently, those effects, i.e. the system’s dynamic behavior, need to be known. For the piezo-composite transducers in an ultrasonic transmission line, a model based approach is used to describe their dynamic behavior and take into account its dependence on the environment temperature and the acoustic impedance of the target medium. Temperature-dependent model parameters are presented, which are obtained by performing a multiplepart identification process on the transducer model, based on electrical impedance measurements [1]. The identification process uses an inverse approach for optimizing a subset of the model parameters. Additionally, algorithmic differentiation methods are used to determine accurate derivatives. In a final optimization step, impedance measurements taken at different temperatures are used to determine the temperature dependencies of the model parameters. These can then be used to assess the plausibility of the identification results. Additionally, the parameters can be expressed as polynomials in the temperature to take different operating conditions into account.
Keywords: piezo-composite; transducer; temperature dependency; identification; plausibility

Implementation and uncertainty analysis of a test device for electrical impedance measurements using vector network analyzers - Webersen, Manuel; Karzellek, Michael; Bause, Fabian; Henning, Bernd

The Complexities of Self-Tracking - An Inquiry into User Reactions and Goal Attainment - Sjjklint, Mimmi; Constantiou, Ioanna D; Trier, Matthias (SSRN Electronic Journal)

GaNm-plane: Atomic structure, surface bands, and optical response - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Neumann, M. D.; Speiser, E.; Esser, N. (Physical Review B)

Liquid Crystal (8CB) Molecular Adsorption on Lithium Niobate Z-Cut Surfaces - Braun, Christian; Sanna, Simone; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Phonon dispersion and zero-point renormalization of LiNbO3 from density-functional perturbation theory - Friedrich, Michael; Riefer, Arthur; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
The vibrational properties of stoichiometric LiNbO3 are analyzed within density-functional perturbation theory in order to obtain the complete phonon dispersion of the material. The phonon density of states of the ferroelectric (paraelectric) phase shows two (one) distinct band gaps separating the high-frequency (~800 cm−1) optical branches from the continuum of acoustic and lower optical phonon states. This result leads to specific heat capacites in close agreement with experimental measurements in the range 0–350 K and a Debye temperature of 574 K. The calculated zero-point renormalization of the electronic Kohn–Sham eigenvalues reveals a strong dependence on the phonon wave vectors, especially near Γ. Integrated over all phonon modes, our results indicate a vibrational correction of the electronic band gap of 0.41 eV at 0 K, which is in excellent agreement with the extrapolated temperature-dependent measurements.

Defect complexes in congruentLiNbO3and their optical signatures - Li, Yanlu; Schmidt, Wolf Gero; Sanna, Simone (Physical Review B)

Modeling atomic force microscopy at LiNbO 3 surfaces from first-principles - Sanna, S.; Dues, C.; Schmidt, Wolf Gero (Computational Materials Science)

Intersecting 1-factors and nowhere-zero 5-flows - Steffen, Eckhard (Combinatorica)

Edge-colorings and circular flow numbers of regular graphs - Steffen, Eckhard (J. Graph Theory)

The difference between the circular and the integer flow number of bidirected graphs - Máčajová, Edita; Steffen, Eckhard (Discrete Mathematics)

1-factor-and cycle covers of cubic graphs - Steffen, Eckhard (J. Graph Theory)

Nowhere-zero flows on signed regular graphs - Schubert, Michael; Steffen, Eckhard (European J. Combinatorics)

Case-Based Reasoning Research and Development - Hüllermeier, Eyke; Minor, M. (in Proceedings 23rd International Conference on Case-Based Reasoning (ICCBR 2015) LNAI 9343)

Proceedings 25. Workshop Computational Intelligence KIT Scientific Publishing - Hoffmann, F.; Hüllermeier, Eyke

Case Base Maintenance in Preference-Based CBR - Abdel-Aziz, A.; Hüllermeier, Eyke (In Proceedings 23rd International Conference on Case-Based Reasoning (ICCBR 2015))

Qualitative Multi-Armed Bandits: A Quantile-Based Approach - Szörényi, B.; Busa-Fekete, Robert; Weng, P.; Hüllermeier, Eyke (In Proceedings International Conference on Machine Learning (ICML 2015))

Dyad Ranking Using A Bilinear Plackett-Luce Model - Schäfer, Dirk; Hüllermeier, Eyke (in Proceedings European Conference on Machine Learning and Knowledge Discovery in Databases (ECML/PKDD))

Superset Learning Based on Generalized Loss Minimization - Hüllermeier, Eyke; Cheng, W. (in Proceedings European Conference on Machine Learning and Knowledge Discovery in Databases (ECML/PKDD))

Weighted Rank Correlation : A Flexible Approach Based on Fuzzy Order Relations - Henzgen, Sascha; Hüllermeier, Eyke (in Proceedings European Conference on Machine Learning and Knowledge Discovery in Databases (ECML/PKDD))

Online Rank Elicitation for Plackett-Luce: A Dueling Bandits Approach - Szörényi, B.; Busa-Fekete, Robert; Paul, Adil; Hüllermeier, Eyke (in Advances in Neural Information Processing Systems 28 (NIPS 2015))

Online F-Measure Optimization - Szörényi, B.; Busa-Fekete, Robert; Dembczynski, K.; Hüllermeier, Eyke (in Advances in Neural Information Processing Systems 28 (NIPS 2015))

A CBR Approach to the Angry Birds Game - El Mesaoudi-Paul, Adil; Hüllermeier, Eyke (in Workshop Proc. 23rd International Conference on Case-Based Reasoning (ICCBR 2015))

Preference-Based Meta- Learning Using Dyad Ranking: Recommending Algorithms in Cold-Start Situations - Schäfer, Dirk; Hüllermeier, Eyke (in Proceedings of the 2015 International Workshop on Meta-Learning and Algorithm Selection (MetaSel@PKDD/ECML))

Locally weighted regression through data imprecisiation - Lu, S.; Hüllermeier, Eyke (Proceedings 25. Workshop Computational Intelligence)

Depth estimation in monocular images: Quantitative versus qualitative approaches - Ewerth, Ralph; Balz, A.; Gehlhaar, J.; Dembczynski, K.; Hüllermeier, Eyke (Proceedings 25. Workshop Computational Intelligence)

IT Project Portfolio Selection in the Presence of Project Interactions - Meier, Christian

On the Activating Power of Gamification – Empirical Evidence from an Online Community - Mutter, Tobias

On the Bayes-Optimality of F-Measure Maximizers - Waegeman, W.; Dembczynski, K.; Jachnik, A.; Cheng, W.; Hüllermeier, Eyke (in Journal of Machine Learning Research)

Does machine learning need fuzzy logic? - Hüllermeier, Eyke (Fuzzy Sets and Systems)

Recovery analysis for adaptive learning from non-stationary data streams: Experimental design and case study - Shaker, Ammar; Hüllermeier, Eyke (Neurocomputing)

From Knowledge-based to Data-driven fuzzy modeling-Development, criticism and alternative directions - Hüllermeier, Eyke (Informatik Spektrum)

Overlap Indices: Construction of and Application of Interpolative Fuzzy Systems - Garcia-Jimenez, S.; Bustince, U.; Hüllermeier, Eyke; Mesiar, R.; Pal, N.R.; Pradera, A. (IEEE Transactions on Fuzzy Systems)

Fast Fuzzy Pattern Tree Learning of Classification - Senge, Robin; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

Mechanism for nuclear and electron spin excitation by radio frequency current - Müllegger, Stefan; Rauls, Eva; Gerstmann, Uwe; Tebi, Stefano; Serrano, Giulia; Wiespointner-Baumgarthuber, Stefan; Schmidt, Wolf Gero; Koch, Reinhold (Physical Review B)

Single PTCDA molecules on planar and stepped KCl and NaCl(100) surfaces - Aldahhak, Hazem; Schmidt, Wolf Gero; Rauls, E. (Surface Science)

Diindenoperylene adsorption on Cu(111) studied with density-functional theory - Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Surface Science)

Interwire coupling forIn(4×1)/Si(111) probed by surface transport - Edler, F.; Miccoli, I.; Demuth, S.; Pfnür, H.; Wippermann, S.; Lücke, A.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Water adsorbate influence on the Cu(110) surface optical response - Baghbanpourasl, Amirreza; Schmidt, Wolf Gero; Denk, Mariella; Cobet, Christoph; Hohage, Michael; Zeppenfeld, Peter; Hingerl, Kurt (Surface Science)

The Cu2O2torture track for a real-life system: [Cu2(btmgp)2O2]2+oxo and peroxo species in density functional calculations† - Rohrmüller, Martin; Hoffmann, Alexander; Thierfelder, Christian; Herres-Pawlis, Sonja; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Nanopatterning on H-Terminated Si(111) Explained as Dynamic Equilibrium of the Chemical Reaction with Methanol - Thissen, Peter; Fuchs, Ehud; Roodenko, Katy; Peixoto, Tatiana; Batchelor, Ben; Smith, Dennis; Schmidt, Wolf Gero; Chabal, Yves (The Journal of Physical Chemistry C)

Influence of Structural Defects and Oxidation onto Hole Conductivity in P3HT - Lücke, A.; Schmidt, Wolf Gero; Rauls, E.; Ortmann, F.; Gerstmann, Uwe (The Journal of Physical Chemistry B)

Barrier-free subsurface incorporation of 3d metal atoms into Bi(111) films - Klein, C.; Vollmers, N. J.; Gerstmann, Uwe; Zahl, P.; Lükermann, D.; Jnawali, G.; Pfnür, H.; Tegenkamp, C.; Sutter, P.; Schmidt, Wolf Gero; Horn-von Hoegen, M. (Physical Review B)

Structure formation in diindenoperylene thin films on copper(111) - Aldahhak, Hazem; Matencio, S.; Barrena, E.; Ocal, C.; Schmidt, Wolf Gero; Rauls, E. (Physical Chemistry Chemical Physics)
First-principles calculations were combined with scanning tunneling microscopy (STM) measurements to analyze the adsorption of diindenoperylene (DIP) molecules on Cu(111) surfaces.

Modeling atomic force microscopy at LiNbO 3 surfaces from first-principles - Sanna, S.; Dues, C.; Schmidt, Wolf Gero (Computational Materials Science)

Structure formation in diindenoperylene thin films on copper(111) - Aldahhak, Hazem; Matencio, S.; Barrena, E.; Ocal, C.; Schmidt, Wolf Gero; Rauls, E. (Physical Chemistry Chemical Physics)
First-principles calculations were combined with scanning tunneling microscopy (STM) measurements to analyze the adsorption of diindenoperylene (DIP) molecules on Cu(111) surfaces.

Polaronic deformation at theFe2+/3+impurity site inFe:LiNbO3crystals - Sanson, A.; Zaltron, A.; Argiolas, N.; Sada, C.; Bazzan, M.; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

GaNm-plane: Atomic structure, surface bands, and optical response - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Neumann, M. D.; Speiser, E.; Esser, N. (Physical Review B)

Sustaining Civil Peace: A Configurational Comparative Analysis - Gries, Thomas; Palnau, Irene (Peace Economics, Peace Science and Public Policy)

Does technological change drive inclusive industrialization? A review of major concepts and findings - Gries, Thomas; Grundmann, Rainer; Palnau, Irene; Redlin, Margarete

A panel of peralkylated sulfur–guanidine type bases: Novel pro-ligands for use in biomimetic coordination chemistry - Neuba, Adam; Rohrmüller, Martin; Hölscher, Rebecca; Schmidt, Wolf Gero; Henkel, Gerald (Inorganica Chimica Acta)